MANAJEMEN PEMBINAAN KARAKTER SISWA/I SMK SARI PUTRA MELALUI KEGIATAN NASIONAL HUT TNI KE-80 - Sopiah, Sopiah (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the management of student character development through participation in national activities, focusing on the involvement of SMK Sari Putra North Jakarta in the 80th Anniversary of the Indonesian National Armed Forces (TNI) at the National Monument, Jakarta. This research employed a descriptive qualitative approach. Data were collected through direct observation, in-depth interviews with school principals, supervising teachers, and participating students, as well as documentation analysis. The results indicate that character development management was implemented through systematic planning, coordinated implementation, and continuous evaluation. Student participation in national activities contributed positively to improvements in discipline, responsibility, leadership, and nationalism. The study concludes that national activities can serve as an effective medium for strengthening student character education when managed in a planned, participatory, and value-oriented manner.